The influence of scanning methods on the cracking failure of thin-wall metal parts fabricated by laser direct deposition shaping. (January 2016) - Ri-sheng, Long; Shao-ni, Sun; Zi-sheng, Lian
Abstract: In order to improve the quality of thin-wall metal parts fabricated by laser direct deposition shaping method, using "element birth and death" technique, a three-dimensional multitrack and multilayer thin-wall model was developed. Different scanning methods, including long-edge parallel reciprocating scanning, short-edge parallel reciprocating scanning and inter-layer orthogonal parallel reciprocating scanning, were researched. The Von Mises equivalent stress, and its X-directional, Y-directional and Z-directional principal stresses were analyzed in detail. Under the same conditions used in the simulations, the deposition experiments were conducted, and the influence of different scanning methods on the cracking failure behavior of thin-wall metal parts was discussed. Highlights: A three-dimension multi- track and multi-1ayer model was developed with APDL. Different scanning methods were taken into account. The thermal behavior under different conditions during LDDS process were obtained. A "thin-plate" method was used to reflect the thermal stress in actual LDDS experiments.